Cardiac tumors—sex‐related characteristics and outcomes after surgical resection. Issue 4 (4th June 2022) - Gaisendrees, Christopher; Gerfer, Stephen; Schlachtenberger, Georg; Walter, Sebastian G.; Ivanov, Borko; Merkle‐Storms, Julia; Mihaylova, Mariya; Sabashnikov, Anton; Djordjevic, Ilija; Rahmanian, Parwis; Mader, Navid; Kuhn‐Régnier, Ferdinand; et al.
Abstract: Objectives: Cardiac tumors represent a rare and heterogeneous pathological entity, with a cumulative incidence of up to 0.02%. Gender was previously reported to influence outcomes after tumor surgery. This study aimed to investigate for gender‐related differences in outcomes after cardiac surgery. Methods: Between 2009 and 2021, 95 male and 88 female patients underwent surgery for tumor extirpation in our center. Preoperative baseline characteristics, intraoperative data, and long‐term survival were analyzed. The diagnosis was confirmed postoperatively by (immune‐)histopathological analysis. Results: There were no significant differences in baseline characteristics and survival. Myxoma was the most common tumor type overall and was more diagnosed in women ( n  = 36 vs. n  = 62, p  ≤ 0.001). Sarcoma was the most common malignant tumor type ( n  = 5). Tumor location at the atrial septum was more likely in women ( n  = 26 vs. n  = 16, p  = 0.041), whereas ventricular localization was more common in male patients ( n  = 20 vs. n  = 7, p  = 0.001). Minimally invasive tumor extirpation was significantly more often performed in women, and in‐hospital stay was shorter in female patients. Conclusion: The localization and dignity of cardiac tumors differ between genders, not affecting survival. Surgical tumor extirpation remains the gold standard of treatment for cardiac tumors in both genders as it is highly effective and associated with good long‐term survivorship.